2019
DOI: 10.1002/ejhf.1534
|View full text |Cite
|
Sign up to set email alerts
|

Definition and treatment of arrhythmogenic cardiomyopathy: an updated expert panel report

Abstract: It is 35 years since the first description of arrhythmogenic right ventricular cardiomyopathy (ARVC) and more than 20 years since the first reports establishing desmosomal gene mutations as a major cause of the disease. Early advances in the understanding of the clinical, pathological and genetic architecture of ARVC resulted in consensus diagnostic criteria, which proved to be sensitive but not entirely specific for the disease. In more recent years, clinical and genetic data from families and the recognition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
112
1
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(119 citation statements)
references
References 77 publications
0
112
1
6
Order By: Relevance
“…18,20 Among the research priorities of the expert panel report on AC is the determination of the role of myocarditis on disease presentation. 7 From our results, it is not possible to affirm that all cardiomyopathy populations are more prone to myocarditis than the general population. Nevertheless, the prevalence of clinically overt AMC appears to be particularly high in our desmosomal variant carriers population,~3/100, in contrast with the usually estimated incidence of myocarditis of one to two per 10 000 per year.…”
Section: Considering Acute Myocarditis In the Diagnostic Workup Of Arcontrasting
confidence: 55%
See 1 more Smart Citation
“…18,20 Among the research priorities of the expert panel report on AC is the determination of the role of myocarditis on disease presentation. 7 From our results, it is not possible to affirm that all cardiomyopathy populations are more prone to myocarditis than the general population. Nevertheless, the prevalence of clinically overt AMC appears to be particularly high in our desmosomal variant carriers population,~3/100, in contrast with the usually estimated incidence of myocarditis of one to two per 10 000 per year.…”
Section: Considering Acute Myocarditis In the Diagnostic Workup Of Arcontrasting
confidence: 55%
“…5 These observations suggest that myocarditis could have a genetic background 6 and raise the question of its implication in the clinical presentation of inherited cardiomyopathies such as AC. 7 However, data regarding genetics in myocarditis are scarce: the management of patients with AMC and their families regarding their risk of having an associated inherited cardiac disease is unclear, and AMC is not mentioned in the guidelines as a criterion to propose a genetic testing. 1,8,9 In order to determine the meaning of the occurrence of AMC in inherited cardiomyopathies, the aim of our study was to analyse the pedigrees and management of prospectively identified families with at least one individual with a documented episode of AMC and at least one individual with a cardiomyopathy or a history of sudden death.…”
Section: Introductionmentioning
confidence: 99%
“…Arrhythmogenic right ventricular cardiomyopathy is a rare cardiovascular disease belonging to a subset of cardiomyopathies known as “arrhythmogenic cardiomyopathies” that each carry a propensity for arrhythmia 4 . First described by Fontaine and colleagues, arrhythmogenic right ventricular cardiomyopathy is now understood as a genetically determined myocardial dystrophy propagated by an autosomal dominant pattern of inheritance, incomplete penetrance, and variable expressivity 5 .…”
Section: Discussionmentioning
confidence: 99%
“…The clinical paradigm of arrhythmogenic right ventricular cardiomyopathy has shifted from that of a right ventricular disease with malignant arrhythmia to a broader disease spectrum including macro‐ and microscopic structural myocardial abnormalities with possible involvement of both ventricles, arrhythmias and a genetic basis, so‐called arrhythmogenic cardiomyopathy. The pathogenesis, clinical characteristics and direction for future research for this relatively new disease entity are outlined in a consensus document …”
Section: Arrhythmogenic Cardiomyopathymentioning
confidence: 99%